KEMITRAAN DAN KNOWLEDGE MANAGEMENT SEBAGAI STRATEGI ADAPTASI PERUBAHAN LINGKUNGAN BISNIS UNTUK MENINGKATKANKEUNGGULAN BERSAING BERKELANJUTAN (Studi Empirik Kemitraan Pemasok Tembakau PT Djarum di Kabupaten Temanggung) - Sofani, Agung; Miyasto, Miyasto; Djastuti, Indi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
Changes in the business environment are unavoidable in an industry. To survive in the competitive, businesses must be able to adapt to changes in the external business environment. The ability of businesses to adapt to the changing business environment becomes a key aspect needed to achieve competitive advantage in the long-term (sustainable) perspective. Based on this phenomenon, the study aims to examine the effect of partnership perspective and knowledge management in building the adaptability of the changing business environment and enhance the sustainable competitive advantage.The data regarding the partnership perspective, knowledge management, adaptation to the business environment and sustainable competitive advantage obtained through interviews using questionnaires. The sample was PT Djarum tobacco suppliers partner in Temanggung. Structural Equation Modeling (SEM) was run by AMOS, the software was used to analyze the data obtained.Statistical analysis showed that the partnership perspective, and knowledge management, positive and significant impact on the adaptability of the business environment changes; adaptability of the business environment changes proved to be positively and significantly impact to sustainable competitive advantage. Directly, partnerships and knowledge management perspective also positively and significantly impact to sustainable competitive advantage.